Confocal Raman imaging of live cells - Zoladek, Alina (2011)
The objective of this thesis is to present the development of Raman microscopy for biochemical imaging of living cells. The main aim was to construct a Raman micro-spectrometer with the ability to perform time-course spectral measurements for the non-invasive study of biochemical processes in individual cells. The work can be divided into two parts: first, the development and characterization of the instrument; and second, completion of two experiments that demonstrate the suitability of Raman technique for studies of live cells. Instrumental development includes the design of optics and software for automated measurement. The experiments involve data collection and development of mathematical methods for analysis of the data.